The elementary forms of digital culture. Knowledge, connections and sociality - Susca, Vincenzo (Education Sciences & Society - Open Access, 2019)
Contemporary communicative platforms welcome and accelerate a socio-anthropological mutation in which public opinion (Habermas, 1995) based on rational individuals and alphabetic culture gives way to a public emotion whose emotion, empathy and sociality are the bases, where it is no longer the reason that directs the senses but the senses that begin to think. The public spheres that are elaborated in this way can only be disjunctive (Appadurai, 2001), since they are motivated by the desire to transgress the identity, political and social boundaries where they have been elevated and restricted. The more the daily life, in its local intension and its global extension, rests on itself and frees itself from projections or infatuations towards transcendent and distant orders, the more the modern territory is shaken by the forces that cross it and pierce it. non-stop. The widespread disobedience characterizing a significant part of the cultural events that take place in cyberspace - dark web, web porn, copyright infringement, trolls, even irreverent ... - reveals the anomic nature of the societal subjectivity that emerges from the point of intersection between technology and naked life. Behind each of these offenses is the affirmation of the obsolescence of the principles on which much of the modern nation-states and their rights have been based. Each situation in which a tribe, cloud, group or network blends in a state of ecstasy or communion around shared communications, symbols and imaginations, all that surrounds it, in material, social or ideological terms, fades away. in the air, being isolated by the power of a bubble that in itself generates culture, rooting, identification: transpolitic to inhabit it.